2021
DOI: 10.1111/apt.16712
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of tofacitinib for treatment of ulcerative colitis: final analysis of OCTAVE Open, an open‐label, long‐term extension study with up to 7.0 years of treatment

Abstract: Summary Background Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis. We present final data from OCTAVE Open, an open‐label, long‐term extension study. Aims The primary objective of OCTAVE Open was to assess the safety and tolerability of long‐term tofacitinib in patients with ulcerative colitis; evaluating efficacy was a secondary objective. Methods Eligible patients included OCTAVE Induction 1&2 non‐responders and OCTAVE Sustain completers/treatment failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 37 publications
11
111
0
5
Order By: Relevance
“…Full study design details for OCTAVE Induction 1 and 2, OCTAVE Sustain and OCTAVE Open have been reported previously. 6,7…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full study design details for OCTAVE Induction 1 and 2, OCTAVE Sustain and OCTAVE Open have been reported previously. 6,7…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the duration of participation for an individual patient may range from approximately 4 years up to 7 years. Full study design details for OCTAVE Induction 1 and 2, OCTAVE Sustain and OCTAVE Open have been reported previously 6,7 …”
Section: Methodsmentioning
confidence: 99%
“…Tofacitinib (anti-JAK) is the latest drug available to treat IBD, in particular UC. Blocking the JAK-STAT pathway, it interferes with the signaling pathways of several cytokines [ 30 ].…”
Section: Therapeutic Management Of Chronic Intestinal Disordersmentioning
confidence: 99%
“…A recent phase 3, multicentre, open-label, long-term extension study (OCTAVE Open) further validated the safety profile of tofacitinib which remained stable when patients were followed up to 7 years, and its efficacy was maintained up to 36 months. 4 Panaccione et al evaluated tofacitinib drug survival and persistence in the OCTAVE Open trial across selected subgroups of patients with differing levels of disease activity at baseline and explored the reasons for treatment discontinuation. 5 The authors observed high levels of tofacitinib treatment persistence across selected subpopulations of patients with a median time to discontinuation ranging from 4.0 to 5.6 years.…”
Section: N V I T E D E D I T O R I a L Editorial: Response To Tofacit...mentioning
confidence: 99%
“…In these studies, tofacitinib was shown to have statistically significant efficacy in induction of remission and mucosal healing at 8 weeks, and in sustained remission and mucosal healing at 52 weeks, compared with placebo. A recent phase 3, multicentre, open‐label, long‐term extension study (OCTAVE Open) further validated the safety profile of tofacitinib which remained stable when patients were followed up to 7 years, and its efficacy was maintained up to 36 months 4 …”
mentioning
confidence: 92%